The ECB's accountability: Adjusting accountability arrangements to the ECB's evolving roles. Issue 1 (February 2019) - Dragomir, Larisa
This article examines the European Central Bank's accountability holistically, ascertaining the multitude of accountability arrangements corresponding to the different tasks, as well as the different angles of accountability with a view to determining the capacity of the existing framework to respond to the frequent calls for increased scrutiny of the European Central Bank's actions in the aftermath of the financial crisis. In this vein, the paper focuses on identifying those elements of the accountability arrangements that are flexible and therefore allow for adjusting the intensity, form and consequences of scrutiny over the European Central Bank's actions in relation to its various functions. The first section identifies the multitude of principals to whom the European Central Bank is accountable when performing its various functions. The second section discusses what the European Central Bank is accountable for, whereas the third section analyses the different legal frameworks that represent benchmarks for holding the European Central Bank accountable in the context of its various functions. The fourth section discusses the channels that allow principals to influence the European Central Bank's behaviour following accountability checks. The last section highlights the resilience inherent in the existing framework, which permits adjusting accountability arrangements to respond to calls for increased accountability. 1